(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
Summary : Poverty is a problem that cannot be postponed to overcome and must be a top priority in the implementation of social welfare development based on the background of the problem, so this study aims to find out what the performance of the Social Welfare Service on the Implementation of Regional Operations Programs to Resolve Poverty in Bitung City. The type of research used in this research is a qualitative approach. This research aims to understand the needs of the poor. The informants in the study were obtained from field visits to the research location by the researcher, namely in the Social Service Office, the method of determining informants was by selecting sources who really knew about problems that occur on the spot so that they will provide information precisely as needed by researchers. The results showed that the preparation of program plans, strategic plans and operational / implementation plans for the ODSK program by the Social Service of Bitung City. The goal is that the planning of the ODK program and its implementation do not overlap but the program runs one way and in harmony starting from the provincial central level to the District and Village levels.